2012
DOI: 10.1016/j.pneurobio.2012.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Neurodegeneration as an RNA disorder

Abstract: Neurodegenerative diseases constitute one of the single most important public health challenges of the coming decades, and yet we presently have only a limited understanding of the underlying genetic, cellular and molecular causes. As a result, no effective disease-modifying therapies are currently available, and no method exists to allow detection at early disease stages, and as a result diagnoses are only made decades after disease pathogenesis, by which time the majority of physical damage has already occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 316 publications
(340 reference statements)
1
38
0
Order By: Relevance
“…Due in part to the gains in knowledge of the human genome, made possible by next-generation sequencing and similar techniques, there is increasing evidence of the involvement of miRNAs in the development of the central nervous system and in neurodegeneration[10]. Recent reports have shown that aberrant miRNA expression contributes to neurodegeneration, and that NDDs may be considered as a class of RNA disorders [11, 12]. The failures of a number of surgical and pharmacological treatments for NDDs highlight the need for novel therapeutic approaches to regulate several targets and molecular pathways.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…Due in part to the gains in knowledge of the human genome, made possible by next-generation sequencing and similar techniques, there is increasing evidence of the involvement of miRNAs in the development of the central nervous system and in neurodegeneration[10]. Recent reports have shown that aberrant miRNA expression contributes to neurodegeneration, and that NDDs may be considered as a class of RNA disorders [11, 12]. The failures of a number of surgical and pharmacological treatments for NDDs highlight the need for novel therapeutic approaches to regulate several targets and molecular pathways.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 99%
“…This would have been impossible in any other transgenic mouse model that uses cDNA to express the mutant ataxin-2. In fact, considering the increasing relevance given to RNA-related mechanisms of toxicity in neurodegenerative diseases, the BAC-Q72 is the most adequate model to study these phenomena in SCA2 (Johnson et al, 2012; Tan et al, 2012; Cleary and Ranum, 2013; Ramaswami et al, 2013). Besides this, the mice also displayed a moderate ataxic phenotype at 16 weeks, with impairments in the accelerated rotarod, which worsened in a progressive manner.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have highlighted the contribution of non-coding RNA molecules, such as anti-sense and long non-coding transcripts, to the pathophysiology of polyQ and other neurodegenerative disorders (Moseley et al, 2006; Ladd et al, 2007; de Mezer et al, 2011). The mechanisms of RNA toxicity in neurodegeneration have been extensively reviewed elsewhere (Johnson et al, 2012; Salta and De Strooper, 2012; Tan et al, 2012) and include the sequestration of RNA-binding proteins, the production of mutant repeat RNA molecules by anti-sense transcription and the modulation of mutated genes by miRNAs. In SCA2, bidirectional transcription of the ATXN2 gene has been recently reported, with the production of a neurotoxic anti-sense transcript ( ATXN2-AS ) as a consequence (Li et al, 2016).…”
Section: Disease Mechanisms Of Sca2mentioning
confidence: 99%
“…Since one miRNA can alter the expression of hundreds of genes, there have been views that NDDs are RNA disorders [63]. Specific miRNAs associated with PD, AD, HD, and ALS are known [64].…”
Section: Mirnas As Factors Of Neuroepigenetics and Biomarkers For Neumentioning
confidence: 99%